Using building information modeling to track and assess the structural condition of bridges - McGuire, Brendan Michael, author; Atadero, Rebecca, advisor; Clevenger, Caroline, advisor; Ozbek, Mehmet, committee member; Elliott, Jonathan, committee member (Colorado State University. Libraries, 2014)
National Bridge Inspection Standards do not require documenting damage location during an inspection but bridge evaluation provisions highlight the importance of it. When determining a safe load carrying capacity of a bridge, damage location information is significant because shear and moment limit states are more critical at different locations and member capacities can vary along the length of a span. Capturing damage location information using current methods can be impractical; however, building information modeling (BIM) provides new opportunities in tracking and utilizing this information. A method and prototype implementation to apply BIM software to the operation and maintenance stages of bridges' service lives is presented. The proposed Bridge information modeling for Inspection and Evaluation Method (BIEM) could allow transportation agencies to more efficiently manage bridge inventories using BIM capabilities while incorporating damage location information. The method, created by the author, uses BIM to document damage type, amount, severity, and location information during a bridge inspection. To leverage this information, inspection results are exported from the BIM model into a spreadsheet where a custom subroutine evaluates the structural performance and performs load ratings on selected bridge superstructure elements. In addition, based on the type, amount, and severity of damage, estimated repair quantities are given and maintenance recommendations are provided. The proposed method was field tested on a case study bridge in Larimer County, Colorado. Official inspection reports and load ratings were obtained and a visual inspection of the bridge utilizing supplemental location-based measurements was performed. The BIEM was implemented and numerical results were compared to the official load ratings. Results suggest that documenting the location of deterioration within a bridge element can affect the guidelines for determining a safe load carrying capacity for a bridge. In addition, the opportunity exists for BIM to play a significant role in bridge management in the future as demonstrated by its proven ability to facilitate the inspection and evaluation processes which could ultimately result in more automated practices. Overall, results from this research motivate future work in the study of deterioration modes and their effect on bridge element capacity and tailoring the principles BIM to the later stages of bridges' service lives.
Keywords: BIM; bridge information modeling; bridge inspection; BrIM; building information modeling; management systems